2021
DOI: 10.1016/j.ebiom.2021.103579
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility study of controlled human infection with Streptococcus pneumoniae in Malawi

Abstract: Background Persistent carriage of pneumococcal vaccine serotypes has occurred after introduction of PCV13 vaccination in Africa but the mechanisms are unclear. We tested the feasibility of using a human pneumococcal challenge model in Malawi to understand immune correlates of protection against carriage and to trial alternative vaccine candidates. We aimed to identify a dose of Streptococcus pneumoniae serotype 6B sufficient to establish nasopharyngeal carriage in 40% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…The 4/9 carriage rate at 80,000 CFUs met our predefined study stopping criteria 4 to confirm CHIM feasibility. This confirms that the 80,000 CFU pneumococcal dose used by LSTM to test vaccines in the UK is relevant to populations within Malawi 8 . Based on successful transfer of procedures, we are confident that our clinical and laboratory procedures are sufficiently robust to test vaccine efficacy.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…The 4/9 carriage rate at 80,000 CFUs met our predefined study stopping criteria 4 to confirm CHIM feasibility. This confirms that the 80,000 CFU pneumococcal dose used by LSTM to test vaccines in the UK is relevant to populations within Malawi 8 . Based on successful transfer of procedures, we are confident that our clinical and laboratory procedures are sufficiently robust to test vaccine efficacy.…”
Section: Introductionsupporting
confidence: 65%
“…Our feasibility study of pneumococcal controlled human infection in Malawi 7 has demonstrated no SAEs or AEs and minimal symptoms for participants who completed the programme 8 . We have confirmed LSTM procedures and successfully adapted standard operating procedures for in-country use.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…137 The group is moving forward with conducting human challenge studies in Malawi. A feasibility study was recently completed, 138 and techniques to study saliva, nasal fluid, nasal microbiopsies, and nasal biopsies have been transferred to Malawi. The studies will address which vaccines can prevent pneumococcal carriage, how effective they are in vulnerable populations, and the mechanisms of respiratory tract defense needed for an effective mucosal vaccine.…”
Section: Rationale For Pneumococcal Challenge Studies In Malawimentioning
confidence: 99%
“…However, since the turn of the century the number of human infection studies conducted has risen dramatically 4 , facilitated in part by significant technological advances that have increased the scientific value of this research. In the last decade there has also been an increase in their geographical spread, with Plasmodium falciparum , and more recently Plasmodium vivax 5 and Pneumococcus 6 challenge studies being conducted in Africa and Asia.…”
Section: Introductionmentioning
confidence: 99%